2021
DOI: 10.1002/pon.5792
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of physical symptom burden and psychological distress during the last year of life in patients with a solid metastatic cancer

Abstract: Objective: To delineate the trajectories of physical symptoms and psychological distress among patients with a solid metastatic cancer during the last year of life. Methods:We used data of 345 decedents from a prospective cohort of 600 patients with a Stage IV solid cancer. Using group-based trajectory modelling, we assessed (a) demographic (age, gender, education, cancer site) predictors of trajectory membership, (b) shift in trajectories associated with planned and unplanned hospitalizations, emergency room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…[3][4][5] These symptoms of terminal illness have mainly been studied and reported independently as discrete entities, with a focus on their prevalence and trajectories. 6 However, clinical observations and some empirical studies show that some symptoms consistently present as clusters, 7 such as fatigue-pain, 8 anxiety-depression-insomnia (neuropsychological), and nausea-vomiting (gastrointestinal). 9 A study of 1562 advanced cancer patients found four consistent clusters using different analysis methods: tense-worry-irritable-depressed, fatigue-pain, nausea-vomiting, and concentration-memory.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] These symptoms of terminal illness have mainly been studied and reported independently as discrete entities, with a focus on their prevalence and trajectories. 6 However, clinical observations and some empirical studies show that some symptoms consistently present as clusters, 7 such as fatigue-pain, 8 anxiety-depression-insomnia (neuropsychological), and nausea-vomiting (gastrointestinal). 9 A study of 1562 advanced cancer patients found four consistent clusters using different analysis methods: tense-worry-irritable-depressed, fatigue-pain, nausea-vomiting, and concentration-memory.…”
Section: Introductionmentioning
confidence: 99%
“…The value of entropy ranged from 0 to 1, and when it was 0.8, it indicated that the classification accuracy was more than 90%. 26 Lo-Mendell-Rubin (LMR) and Bootstrapped Likelihood Ratio Test (BLRT) were used to compare the difference in fit between the models. If both P values reached a significant level, the model with k classes was significantly better than that with k-1 classes.…”
Section: Methodsmentioning
confidence: 99%
“…Six studies included only women with advanced stage cancer: three ovarian, one cervical, and two included various cancer sites (gynecological cancers grouped together, and ovarian cancer in addition to other cancers). 23,33,39,44,50,54 Most studies (n = 18; 86%) were quantitative, and two-thirds of the studies were conducted in either Asia, Australia, or Europe. The recruitment of study participants spanned from 1987 to 2021.…”
Section: Study Characteristicsmentioning
confidence: 99%